Zarządzanie oświatą w turbulentnym otoczeniu - Banaszak, Sławomir (Wydawnictwo Naukowe UAM, 2013)
Management of education is a very important issue of modern societies. The paper is an attempt at showing turbulence in the processes of managing educational institutions. The author points at changes of the environment of education system as a main problem in the processes. Problems of instability of educational law and the issue of competences of educational institutions managers are revealed. The paper ends with the approach to the problems of effi ciency in management of education and finding the need to change of existing order.
Education management in turbulent environment
Keywords: management of education; management of educational institutions; turbulent environment of education system; competences of managers